(untitled) (Scripta : English Department Journal, 2023)
Self-efficacy and speaking anxiety are viewed as influential factors in learning English for foreign language. In investigating these factors, the researchers are inspired to uncover the relationship between self-efficacy and speaking anxiety faced by non-English department students in STKIP Hamzar, North Lombok. Moreover, this study applied quantitative approach with correlational analysis. In conducting this researcher, 88 non-English department students were involved in this study. They were asked to fulfill two kinds of questionnaires (self-efficacy and speaking anxiety). Based on the result of the study, obtained by the correlation coefficient of - 0.642, it can be concluded that there is a high negative relationship between self-efficacy and speaking anxiety in non-English department students. In other words, the lower self-efficacy that students have, the higher speaking anxiety they faced.